From eyes‐closed to eyes‐open: Role of cholinergic projections in EC‐to‐EO alpha reactivity revealed by combining EEG and MRI. Issue 2 (25th September 2018) - Wan, Lu; Huang, Haiqing; Schwab, Nadine; Tanner, Jared; Rajan, Abhijit; Lam, Ngoc B.; Zaborszky, Laszlo; Li, Chiang‐shan R.; Price, Catherine C.; Ding, Mingzhou
Abstract: Alpha rhythm (8 to 12 Hz) observed in EEG over human posterior cortex is prominent during eyes‐closed (EC) resting and attenuates during eyes‐open (EO) resting. Research shows that the degree of EC‐to‐EO alpha blocking or alpha desynchronization, termed alpha reactivity here, is a neural marker of cognitive health. We tested the role of acetylcholine in EC‐to‐EO alpha reactivity by applying a multimodal neuroimaging approach to a cohort of young adults and a cohort of older adults. In the young cohort, simultaneous EEG‐fMRI was recorded from twenty‐one young adults during both EO and EC resting. In the older cohort, functional MRI was recorded from forty older adults during EO and EC resting, along with FLAIR and diffusion MRI. For a subset of twenty older adults, EEG was recorded during EO and EC resting in a separate session. In both young and older adults, functional connectivity between the basal nucleus of Meynert (BNM), the major source of cortical acetylcholine, and the visual cortex increased from EC to EO, and this connectivity increase was positively associated with alpha reactivity; namely, the stronger the BNM‐visual cortex functional connectivity increase from EC to EO, the larger the EC‐to‐EO alpha desynchronization. In older adults, lesions of the fiber tracts linking BNM and visual cortex quantified by leukoaraiosis volume, associated with reduced alpha reactivity. These findings support a role of acetylcholine and particularly cholinergic pathways in mediating EC‐to‐EO alpha reactivity and suggest that impaired alpha reactivity could serve as a marker of the integrity of the cholinergic system.